Association of promoter region A-1012G polymorphism (rs4516035) of vitamin-D receptor gene with coronary artery disease - Nazar, Shazia; Ahmed Khan, Taseer; Sitwat Zehra (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the correlation of Adenine-1012-Guanine (rs4516035) promoter region polymorphism of vitamin-D receptor gene with serum levels of omentin-1, vitamin-D and vitamin-D receptor protein in patients with coronary artery disease. Method: The case-control study was conducted January to June 2020 at the cardiac unit of Civil hospital Karachi (CHK), and comprised coronary artery disease patients and controls. The tetra-primer amplification refractory mutation system polymerase chain reaction method was used to genotype Adenine-1210Guanine polymorphism in the vitamin D receptor gene. Serum levels of omentin-1, vitamin-D, and vitamin-D receptor protein were measured in both the groups using an enzyme-linked immunosorbent assay. Data was analysed using SPSS 17. Results: Of the 1,000 subjects, there were 500(50%) cases; males 306(61.2%) and 194(38.8%) females with overall mean age of 51.08±9.55 years. The remaining 500(50%) were controls; 290(58%) males and 210(42%) females with overall mean age of 50.9±10.78 years. The mutant Guanine allele was more prevalent in controls 261(52.2%), and had a non-significant correlation with coronary artery disease (p=0.45). Among the cases, the wild Adenine-Adenine genotype had a higher prevalence 402(80.4%) and had a significant correlation with coronary artery disease (p<0.001). The heterozygous genotype Adenine-Guanine was significantly more predominant among the controls 346(69.2%) compared to the cases 66(13.2) (p=0.002). Conclusion: Adenine-1012-Guanine polymorphism in the vitamin-D receptor gene was found to be a protective polymorphism for coronary artery disease in the recessive model. Key Words: Coronary artery disease, Omentin-1, Vitamin-D, Vitamin-D receptor.